Gut microbiota-based vaccination engages innate immunity to improve blood glucose control in obese mice - Brittany M. Duggan; Akhilesh K. Tamrakar; Nicole G. Barra; Fernando F. Anhê; Gabriella Paniccia; Jessica G. Wallace; Hannah D. Stacey; Michael G. Surette; Matthew S. Miller; Deborah M. Sloboda; Jonathan D. Schertzer (Elsevier, 2022)
Objective: Obesity and diabetes increase circulating levels of microbial components derived from the gut microbiota. Individual bacterial factors (i.e., postbiotics) can have opposing effects on blood glucose. Methods: We tested the net effect of gut bacterial extracts on blood glucose in mice using a microbiota-based vaccination strategy. Results: Male and female mice had improved glucose and insulin tolerance five weeks after a single subcutaneous injection of a specific dose of a bacterial extract obtained from the luminal contents of the upper small intestine (SI), lower SI, or cecum. Injection of mice with intestinal extracts from germ-free mice revealed that bacteria were required for a microbiota-based vaccination to improve blood glucose control. Vaccination of Nod1−/−, Nod2−/−, and Ripk2−/− mice showed that each of these innate immune proteins was required for bacterial extract injection to improve blood glucose control. A microbiota-based vaccination promoted an immunoglobulin-G (IgG) response directed against bacterial extract antigens, where subcutaneous injection of mice with the luminal contents of the lower SI elicited a bacterial extract-specific IgG response that is compartmentalized to the lower SI of vaccinated mice. A microbiota-based vaccination was associated with an altered microbiota composition in the lower SI and colon of mice. Lean mice only required a single injection of small intestinal-derived bacterial extract, but high fat diet (HFD)-fed, obese mice required prime-boost bacterial extract injections for improvements in blood glucose control. Conclusions: Subversion of the gut barrier by vaccination with a microbiota-based extract engages innate immunity to promote long-lasting improvements in blood glucose control in a dose-dependent manner.